Days on earth : the dance of Doris Humphrey - Siegel, Marcia B. (Duke University Press, 1993)
Now available in paperback, Days on Earth--originally published in 1988 (Yale University Press)--traces the dance career and artistic development of one of the founders of American modern dance. In this biography of dance pioneer Doris Humphrey, Marcia B. Siegel follows Humphrey's career from her days with the Denishawn Company (among fellos students like Martha Graham) to her creative partnership with Charles Weidman to her tenure as artistic director of protégé José Limon's dance company. Siegel's reconsideration and description of Humphrey's dances, including many that are no longer performed, sheds important light on this pathbreaking dancer/choreographer.